1997
DOI: 10.1021/jp963339+
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of α-Amino Acids Disubstituted at the α-Carbon

Abstract: The conformational preferences of dipeptides from α-aminoisobutyric acid (Aib), 1-aminocyclopropane-1-carboxylic acid (Ac3c), and 1-aminocyclobutane-1-carboxylic acid (Ac4c) residues have been determined by ab initio quantum mechanical calculations. The results obtained evidence for the intrinsic helix-forming tendency of the Aib residue. Furthermore, the conformational preferences of Ac3c and Ac4c dipeptides are reported and the differences explained in terms of the size of their cyclic side chains. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 38 publications
7
63
0
Order By: Relevance
“…Among the Ac n c series, the intrinsic conformational propensities of the cyclopropane (Ac 3 c), cyclobutane (Ac 4 c), cyclopentane (Ac 5 c), and cyclohexane (Ac 6 c) members (Figure 1) have been extensively investigated. [11][12][13][16][17][18][19][20][21] Results indicated that the preferences of these amino acids strictly parallel those of Aib, i.e. they induce folded structures in the 3 10 -/ R-helix region ( ,Ψ ≈ (60°, (30°), with some distortion in the case of Ac 3 c, which prefers the spatially close bridge region ( ,Ψ ≈ (80°, (0°).…”
Section: Cyclic α-Tetrasubstituted Amino Acidsmentioning
confidence: 93%
“…Among the Ac n c series, the intrinsic conformational propensities of the cyclopropane (Ac 3 c), cyclobutane (Ac 4 c), cyclopentane (Ac 5 c), and cyclohexane (Ac 6 c) members (Figure 1) have been extensively investigated. [11][12][13][16][17][18][19][20][21] Results indicated that the preferences of these amino acids strictly parallel those of Aib, i.e. they induce folded structures in the 3 10 -/ R-helix region ( ,Ψ ≈ (60°, (30°), with some distortion in the case of Ac 3 c, which prefers the spatially close bridge region ( ,Ψ ≈ (80°, (0°).…”
Section: Cyclic α-Tetrasubstituted Amino Acidsmentioning
confidence: 93%
“…The conformational space of Ac-Tris-NHMe was compared with our previous results, 15,16 including Ac-PCU-NHMe, Ac-Ala-NHMe, Ac-Gly-NHMe, and Ac-Aib-NHMe (see Supplementary Material). Glycine tends to favor extended conformations and alanine exhibit some helical conformations, while the conformations of aminoisobutyric acid 16,[32][33][34] are very similar to that exhibited by Ac-Tris-NHMe. Interestingly, the intramolecular hydrogen bond predicted for the C 7 conformation of the Aib dipeptide (H. .…”
Section: Figurementioning
confidence: 83%
“…More specifically, in such two engineered peptides, the D-Phe was replaced by D-Pro while the L-Pro was changed by two conformationally restrained residues. In the first peptide, hereafter denoted GA-S1 (with sequence cyclo(Val-Orn-Leu-D-Pro-Ac3c)2), L-Pro was replaced by 1-aminocyclopropanecarboxylic acid (Ac3c in Scheme 1), an α,α-dialkylated amino acid with strong stereochemical constraints [40,41]. The second peptide (with sequence cyclo(Val-OrnLeu-D-Pro-S,S-c3diPhe)2), hereafter denoted GA-S2, was designed using an Ac3c derivative with two vicinal phenyl substituents in a trans relative disposition (S,S-c3diPhe in Scheme 1) to replace L-Pro.…”
Section: Introductionmentioning
confidence: 99%